2020
DOI: 10.1080/20008198.2020.1767349
|View full text |Cite
|
Sign up to set email alerts
|

Sleep disturbance in post-traumatic stress disorder (PTSD): a systematic review and meta-analysis of actigraphy studies

Abstract: Background: Sleep disturbance has been described as a 'hallmark' symptom of posttraumatic stress disorder (PTSD). Although there are robust findings of self-reported sleep disturbance in PTSD, evidence of sleep disturbance measured using actigraphy is less certain. Objective: To conduct a systematic review and meta-analysis to determine whether there are any significant differences between individuals with and without PTSD in actigraphderived sleep measures. Method: Case-control studies comparing participants … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
16
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(19 citation statements)
references
References 55 publications
3
16
0
Order By: Relevance
“…Sleep and leisure activity were indispensable daily behaviours for regulating psychological stress. A systematic review and meta‐analysis has confirmed sleep quality was impaired in individuals with higher PTSD symptoms (Lewis et al, 2020). The studies conducted in COVID‐19 pandemic also have reported sleep quality was negatively correlated with PTSD symptoms in general HCWs and residents from hardest‐hit area (Liu et al, 2020; Yin et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…Sleep and leisure activity were indispensable daily behaviours for regulating psychological stress. A systematic review and meta‐analysis has confirmed sleep quality was impaired in individuals with higher PTSD symptoms (Lewis et al, 2020). The studies conducted in COVID‐19 pandemic also have reported sleep quality was negatively correlated with PTSD symptoms in general HCWs and residents from hardest‐hit area (Liu et al, 2020; Yin et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…This strengthens the assumption that subjective sleep quality is associated with the level of psychopathology rather than objective sleep quality, and is in line with previous results on patients with ED [ 33 , 34 , 38 , 68 ]. The discrepancies between subjective complaints of sleep disorders and electroencephalogram (EEG) findings are commonly seen in studies on patients with post-traumatic stress disorder (PTSD) [ 71 , 72 ]. These may be related to the traumatic life events associated with ED in general [ 13 ] and ED with NES in particular [ 12 ].…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, this finding is consistent with previous studies reporting an association between decreased sleep continuity and cognitive decline. 21,[53][54][55][56][57] The association between sleep and trauma-related symptoms has been widely studied, 58,59 and REM sleep and SWS have been found to play a role in altered cognitive performance in traumatized people. [59][60][61] Furthermore, a relationship has been established between reduced arousal during sleep and adaptive cognitive processing of traumatic experiences.…”
Section: Discussionmentioning
confidence: 99%